Suspicion in sales and loans between Sharia and law (Journal of the College of Basic Education, 2022)
There is no doubt that transactions are of great importance in societies. Because the general public needs it, and it is based on foundations, conditions, and pillars known and established by the Lawgiver, and these transactions may cause legal problems that lead to the occurrence of suspicion, and this suspicion may in turn lead to forbidden or disliked. When we researched this topic, we dealt with the details and subtleties of the topic as follows: Statement of the linguistic and terminological definition of sale and loan, legality, conditions and elements, then mention the legal article that mentioned that contract, then conclude the request by mentioning the suspicions contained in that contract. The nature of the research necessitated that I divide it into an introduction, followed by two chapters: The first topic included the definition of sale in language and terminology in Sharia and law, the legality of sale, its elements and conditions